Combined maximum‐quantum and DOSY 3D experiments provide enhanced resolution for small molecules in mixtures. (24th July 2016) - Manjunatha Reddy, G. N.; Yemloul, Mehdi; Caldarelli, Stefano
Abstract : We illustrate here as the combination of high‐order maximum‐quantum (MaxQ) and Diffusion‐Ordered SpectroscopY (DOSY) NMR experiments in a 3D layout allows superior resolution for crowded NMR spectra. Non‐uniform sampling (NUS) allows compressing the experimental time effectively to reasonable durations. Because diffusion effects were encoded within multiple‐quantum coherences, increased sensitivity to magnetic field gradients is observed, requiring compensation for convection effects. The experiment was demonstrated on the spectra of a mix of small polyaromatic molecules. Specifically, in the case analyzed, the experiment provided an extreme simplification through the MaxQDOSY‐MaxQ projection plane that presents one peak per molecule. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We illustrate here as the combination of high‐order maximum‐quantum and diffusion‐ordered spectroscopy experiments in a 3D layout allows superior resolution for crowded nuclear magnetic resonance spectra. The experiment was demonstrated on the spectra of a mix of small polyaromatic molecules. Specifically, in the case analyzed, the experiment provided an extreme simplification through the MaxQDOSY‐MaxQ projection plane that presents one peak per molecule.